Nutrients, chlorophyll and biotic metrics in the Rappahannock River-Estuary: implications of urbanization in the Chesapeake Bay Watershed, USA - Prasad, M.B.K.; Maddox, M.C.; Sood, Aditya; Kaushal, S. (Commonwealth Scientific and Industrial Research Organisation, 2014)
In the Chesapeake Bay watershed, various endeavors such as the inter-state agreements and Chesapeake 2000 agreement have been implemented to improve water quality and ecological conditions which have produced mixed results at best in various tributaries. In order to evaluate the management efforts on ecological conditions in the Rappahannock River watershed, we analyzed the long-term variability in land-use, nutrient content, and ecological biotic metrics. It appears that the interannual variability in nutrient loadings and concentrations are largely influenced by changes in urbanization and climate. Significant increases in urban development (35%) and population growth have exacerbated both point and non-point nutrient pollution in the Rappahannock River. Comparatively low N:P ratio in the tidal zone than the non-tidal zone may be due to salinity induced phosphorus leaching from sediments regulating the water quality along the river-estuary continuum. In addition, interannual variability in ecological biotic metrics demonstrates degrading ecological conditions in the Rappahannock River watershed, which are primarily due to increasing watershed urbanization driving high nutrient loadings and altered nutrient stoichiometry.